Laparoscopic subtotal gastrectomy for the treatment of advanced gastric cancer: a comparison with open procedure at the beginning of the learning curve. - Marchesi, Federico; de Sario, Giuseppina; Cecchini, Stefano; Tartamella, Francesca; Riccò, Matteo; Romboli, Andrea (Acta Biomedica Atenei Parmensis, 2017)
Background: In the last decades, after some initial concern, laparoscopic subtotal gastrectomy (LSG) is gaining popularity also for the treatment of advanced gastric cancer (AGC). The aim of this study is to compare a single surgeon initial experience on LSG and open subtotal gastrectomy in terms of surgical safety and radicality, postoperative recovery and midterm oncological outcomes. Methods: a case control study was conducted matching the first 13 LSG for AGC with 13 open procedures performed by the same surgeon. Operative and pathological data, postoperative parameters and midterm oncological outcomes were analyzed. Results: There was no significant difference in mortality (0%) and morbidity, while the laparoscopic approach allowed lower analgesic consumption and faster bowel movement recovery. Operation time was significantly higher in LSG patients (301.5 vs 232 min, p: 0.023), with an evident learning curve effect. Both groups had a high rate of adequate lymph node harvest, but the number was significantly higher in LSG group (p: 0.033). No significant difference in survival was registered. Multivariate analysis identified age at diagnosis, diffuse-type tumor, pN and LODDS as independent predictors of worse prognosis. Conclusions: LSG can be safely performed for the treatment of AGC, allowing faster postoperative recovery.